THE EFFECT OF DIGITAL PAYMENT, DIGITAL TRANSFORMATION, AND DIGITAL BANKING ON FINANCIAL PERFORMANCE OF MSMES IN KOTA JUANG DISTRICT, BIREUEN REGENCY - Nurlela; Chairil Akhyar; Muchsin; Salsabila Prina Wahyuni (Universitas Efarina, 2025)
This study aims to analyze the effect of Digital Payment, Digital Transformation, and Digital Banking on the financial performance of Micro, Small, and Medium Enterprises (MSMEs) in Kota Juang Subdistrict, Bireuen Regency. A quantitative technique based on a survey methodology was used in this research. A total of 1,245 micro-enterprises operating in the trade sector formed the research population. A purposive sampling approach was employed to select 93 businesses, with proportions determined using the Slovin formula. Questionnaires served as the primary data source, which were then analyzed using multiple linear regression analysis in SPSS. The findings indicate that the financial performance of MSMEs is positively and significantly influenced by digital payments. Meanwhile, digital banking and digital transformation show a smaller yet positive impact on financial performance. The limited utilization of digital technology and banking services among micro-enterprises suggests that these factors have not yet had a significant effect in improving their financial performance.